2020
DOI: 10.1002/saj2.20016
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity of mineral soils relates linearly to air‐filled porosity

Abstract: Soil thermal conductivity (λ) depends largely on the volume fractions of soil solids, air and water. Previous studies focus mainly on developing saturation or soil water content (θ) dependent λ models. There are reports that λ is correlated more with air‐filled porosity (na) than with θ, and the correlation is less affected by solid fraction and λ of soil solids. In this study, a simple linear relationship between λ and na is developed with both newly measured and published datasets. Independent evaluations sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Although the effects of θ tot , v s , ρ b , salt concentration, and organic matter content on λ of unfrozen and partially frozen soils have been investigated (Abu‐Hamdeh & Reeder, 2000; Mustamo, Ronkanen, Berglund, Berglund, & Kløve, 2019; Zhao & Si, 2019), no universal relationship has been established between λ and these variables. Alternately, in unfrozen soils, λ has been observed to exhibit a general linear correlation with n a across a wide range of textures (Ochsner et al., 2001; Tong et al., 2019; Xie et al., 2019). Figure 2 illustrates λ as a function of θ tot , v s , or n a for 28 partially frozen soils.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the effects of θ tot , v s , ρ b , salt concentration, and organic matter content on λ of unfrozen and partially frozen soils have been investigated (Abu‐Hamdeh & Reeder, 2000; Mustamo, Ronkanen, Berglund, Berglund, & Kløve, 2019; Zhao & Si, 2019), no universal relationship has been established between λ and these variables. Alternately, in unfrozen soils, λ has been observed to exhibit a general linear correlation with n a across a wide range of textures (Ochsner et al., 2001; Tong et al., 2019; Xie et al., 2019). Figure 2 illustrates λ as a function of θ tot , v s , or n a for 28 partially frozen soils.…”
Section: Resultsmentioning
confidence: 99%
“…Ochsner, Horton and Ren (2001), however, observed that the air‐filled porosity ( n a ), rather than θ w and ρ b , had a dominant effect on λ of unfrozen soils. Xie, Lu, Ren, and Horton (2019) showed that, for unfrozen soils, the λ and n a relationship could be approximated using a general linear function. For partially frozen soils, the n a is approximated by the difference between soil porosity (η) and total water content (θ tot ) because liquid water and ice have fairly similar densities (about 1 and 0.92 Mg m −3 , respectively), which differ substantially from that of the soil solid phase (about 2.65 Mg m −3 for many mineral soils).…”
Section: Introductionmentioning
confidence: 99%
“…First, SUTRA calculates the subsurface bulk thermal conductivity with a weighted arithmetic mean from the thermal conductivities of constituents of the porous matrix (i.e., soil particles and water), but not the air phase. However, the arithmetic mean is not considered to be the correct estimation of soil bulk thermal conductivity [ 39 ] and ignoring the air phase may amplify these inaccuracies [ 40 ]. The SUTRA bulk thermal conductivity equation ( K ) was modified to integrate the air phase with a weighted harmonic mean [ 39 ]: where ε is porosity, S L is water saturation, and K L , K A , and K S are the thermal conductivities of water, air phase, and soil particles, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The authors concluded that the soil thermal property values and the soil AP exhibited simple linear relationships. The λ-AP linear relationship was verified by Xie et al (2020) who pointed out that it could be applied potentially in land surface models for estimating λ from θ and ρ b .…”
mentioning
confidence: 85%